Automobile pollution control in Brazil - Claudio A. Ferraz do Amaral; Ronaldo Serôa da Motta (Institute for Applied Economic Research (ipea), 2015)
Air pollution concentrations have been rapidly increasing in the major urban areas of Brazil caused mainly by the increasing use of vehicles. In the presence of this negative externality, environmental regulation is required. Car emission control policies in Brazil have relied basically on mandatory emission standards and subsidies for specific cleaner technology resulting in substantial decrease of car emission rates. Nevertheless, car sale taxes, differentiated by vehicles' size and fuel, have also influenced car emission patterns. This paper analyzes the compliance trend of the Brazilian fleet with environmental standards between 1992 and 1997. We find that larger automobiles had the fastest compliance schedule while popular models adjusted very slowly. Also gasoline-fueled models had a faster adjustment pattern than ethanol cars. Additionally, we analyze the current relationship between pollution emissions and car characteristics in order to orient policy formulation. We find a positive relationship between emissions rates and horse power, concluding that although the current value added-sale car tax is not environmental harmful, a tax differentiating clean from dirty models, within each tax bracket, could create substantial incentives for emission control in the future.
Keywords: 330